Image Compression in Computer Graphics Using Fractal and Wavelet Analysis (MATEMATIKA, 2012)
Research in computer graphics has recently seen considerable activity centered around the use of wavelets and fractals. Fractal-based image coding is based on the theory of iterated function systems (IFS) and is used for image compression. It is very important to give a powerful computer method that can process up to code and decode quickly and high quality (both together). In this article we show how to use the wavelet analysis and fractal geometry in computer graphics and image compression and also how to use them to break down one dimensional function. Keywords: Wavelet analysis; image compression; fractal; fix point 2010 Mathematics Subject Classification: Primary 62H35; secondary 43A77